(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The article examines the transformations of informed consent in the context of the Covid-19 pandemic, analysing the bioethical discussion and in particular the national and international documents relevant to bioethical and biolegal issues, in both institutional bodies and bioethics committees. Informed consent is analysed in the context of experimentation with treatments and vaccines, the use of biological samples and the processing of personal data.